A LEGITIMIDADE ATIVA PARA OS DIREITOS COLETIVOS NO ESTATUTO DA PESSOA COM DEFICIÊNCIA (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The article takes care of the active legitimacy for the exercise of the transindividual rights contained in the Statute of the Disabled Person. In order to demonstrate that the rights of the people of this protected group are recognized as human rights and because they are diffuse and collective rights they receive different treatment from the classic division in the doctrine regarding the legitimacy for the exercise of protection. Taking into account the procedural system in force, the text shows the existing positions, in the doctrine and the Judiciary, for the filing of collective actions, with interest in predicting the effectiveness of the protection. And with the utmost respect for these standards, which are part of a collective procedural microsystem, all for the purpose of improving the effectiveness and enforcement of the rights of persons with disabilities.